2002
DOI: 10.1046/j.1528-1157.2002.48701.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluoxetine and TFMPP on Spontaneous Seizures in Rats with Pilocarpine‐induced Epilepsy

Abstract: Summary:Purpose: Fluoxetine is a selective serotonin [5-hydroxytryptamine (5-HT)] reuptake inhibitor (SSRI) commonly used to treat depression. Some uncontrolled clinical studies have reported that SSRIs increase seizures, but animal experiments with evoked-seizure models have suggested that SSRIs at therapeutic doses decrease seizure susceptibility. We tested the hypothesis that fluoxetine and trifluoromethylphenylpiperazine (TFMPP, a nonselective 5-HT-receptor agonist) reduce the frequency of spontaneous moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 42 publications
3
53
1
Order By: Relevance
“…However, the 1-and 2-year animals were monitored for two separate time periods and had a mean seizure frequency of 3.6 seizures per day. Although these seizure frequencies are only estimates of the actual seizure frequency over long time periods, they are comparable with the observations from other major laboratories using the pilocarpine model of AE: Pitkanen and co-workers have reported a frequency of 2.6 seizures per day (Goffin et al, 2007); Holmes and co-workers have reported 5.2 seizures per 42 h (Cha et al, 2004), and Dudek and coworkers have reported 6.9 seizures per day (Hernandez et al, 2002). Seizure durations are relatively short (35-50 s) in the pilocarpine model and animals have been shown to tolerate several brief seizures per day without significant behavioral effects (Goffin et al, 2007).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the 1-and 2-year animals were monitored for two separate time periods and had a mean seizure frequency of 3.6 seizures per day. Although these seizure frequencies are only estimates of the actual seizure frequency over long time periods, they are comparable with the observations from other major laboratories using the pilocarpine model of AE: Pitkanen and co-workers have reported a frequency of 2.6 seizures per day (Goffin et al, 2007); Holmes and co-workers have reported 5.2 seizures per 42 h (Cha et al, 2004), and Dudek and coworkers have reported 6.9 seizures per day (Hernandez et al, 2002). Seizure durations are relatively short (35-50 s) in the pilocarpine model and animals have been shown to tolerate several brief seizures per day without significant behavioral effects (Goffin et al, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…One animal demonstrated a cluster of high seizure frequencies and skewed the data to reflect a higher mean seizure frequency for this group. For long-term studies, animals were monitored two times at 12 and 24 months following SE and were found to have a mean seizure frequency of 0.9 ± 0.4 seizures per 6 h. The seizure frequencies observed in this study were comparable to those seen in other studies employing the pilocarpine model (Goffin et al, 2007;Hernandez et al, 2002;Cha et al, 2004;Wallace et al, 2003).…”
Section: Epileptogenesis Causes a Permanent Decrease In Hippocampal Csupporting
confidence: 79%
“…Experimental serotonin treatment hyperpolarizes both pyramidal and granule cells, with the effect possibly occurring directly on principal cells, or mediated by excitation of interneurons (Freund and Buzsaki, 1996). Accordingly, treatment with the SSRI fluoxetine can lead to a general inhibition of hippocampal network activity and, indeed, animal experiments suggest that SSRIs at therapeutic doses are able to decrease seizure susceptibility of the hippocampus (Wada et al, 1995;Hernandez et al, 2002). Thus, in our case, fluoxetine treatment may provide sufficient counterbalancing inhibition to the overexcited hippocampal circuitry, and thereby prevent the compensatory downregulation of parvalbumin to enhance GABA release.…”
Section: Antidepressant Treatment Can Counteract the Effect Of Stressmentioning
confidence: 99%
“…Thus, antidepressant drugs which increase the availability of monoamine neurotransmitters in the synaptic cleft have been associated both with proconvulsant and anticonvulsant effects (Jobe and Browning 2005;Hernandez et al 2002).…”
Section: Introductionmentioning
confidence: 99%